Tryptophan and arginine catabolic enzymes and regulatory cytokines in clinically isolated syndrome and multiple sclerosis. Issue 8 (16th August 2018) - Cha, Lilian; Jones, Anderson P; Trend, Stephanie; Byrne, Scott N; Fabis‐Pedrini, Marzena J; Carroll, William M; Lucas, Robyn M; Cole, Judith M; Booth, David R; Kermode, Allan G; Hart, Prue H
Abstract: Objectives: Clinically isolated syndrome (CIS) is the earliest clinical episode in multiple sclerosis (MS). A study of circulating cells from patients with CIS may help us understand the transition to, and processes associated with, the development of MS. Methods: As immune cell activity can be determined by flux through metabolic pathways, the mRNA expression ofl ‐tryptophan‐ andl ‐arginine‐catabolising enzymes, indoleamine 2, 3‐dioxygenase (IDO) 1 and IDO2 and arginase (ARG) 1 and ARG2, respectively, was compared between peripheral blood mononuclear cells (PBMCs) from healthy controls, and patients with CIS and definite MS. As one measure of cell function, cytokine mRNA levels were analysed directly ex vivo and in cells after culture for 4 h in the absence of regulatory factors in autologous serum. Results: When measured directly ex vivo, the expression of IDO and ARG was greater in cells from patients with CIS and MS than cells from healthy controls. Although not linked to IDO and ARG expression, PBMCs from the CIS patients were characterised by low IL‐10 and TGFB mRNA levels and not by greater expression of proinflammatory cytokines. When the cells were cultured for 4 h without autologous serum, pro‐ and anti‐inflammatory cytokine mRNA levels positively correlated with IDO1 expression, and TGFB mRNA levels correlated with ARG1 expression. Conclusion: Higher IDO and ARG expression in CIS and MS provides one sustained homeostatic mechanism to control MS‐associated inflammation. However, potent extrinsic mediators in serum may regulate immune cell function in CIS and associations between IDO, ARG and cytokine expression. Abstract : Clinically isolated syndrome (CIS) is the earliest clinical episode in multiple sclerosis (MS). Reported changes in the tryptophan and arginine catabolic enzymes and regulatory cytokines in the circulating cells from patients with CIS, in comparison with those of cells from healthy controls and patients with MS, and the effect of extrinsic mediators in serum, should assist an understanding of the transition to, and processes associated with, the development of MS.